Financial management of Harvard university: A common size analysis and implications for Indonesian higher education institutions - Chusniyah, Atin; Munadi, Muhammad (UIN Raden Mas Said Surakarta, 2023)
This study aims to (1) determine Harvard University’s financial management strategy using the common size analysis approach in Harvard University’s balance sheet report for the fiscal year 2020-2022; and (2) examine its implications for Indonesian higher education institutions. The analysis is described from 3 perspectives: the perspective of assets, liabilities, and net assets. The research design uses a descriptive quantitative approach. The primary data source is the Annual Financial Report for Years 2020-2022. The analysis technique used is the analysis of common size. The results of this study indicate that from an asset perspective, attention is paid to managing liquidity, investment, and fixed assets. The importance of debt management, deferred income management, and long-term debt monitoring is highlighted from a liability perspective. From a net asset perspective, the strategy includes allocating operational resources, an endowment fund, and project management of profit-sharing agreements. This analysis provides valuable insights for Indonesian higher education institutions in developing financial management strategies. The limitation of this research is the limited focus on the analysis of balance sheet reports from the perspective of assets, liabilities, and net assets of Harvard University. This study does not consider external factors or other variables that may affect the University’s financial management strategy more comprehensively.